Development of Learning Media for Pneumatic Control Systems for Separation and Transportation of Goods Based on Programmable Logic Controller (PLC) - Akbar, Muhammad; Najib, Nandy Rizaldy; Aldi, Aldi; Hamdani, Hamdani (Jurnal Teknologi Elekterika, 2024)
Pneumatic systems have advantages compared to other systems, pneumatic systems can support quality, productivity and efficiency of work. The research process starts from designing, developing existing tools to testing pneumatic system tools controlled using PLC and HMI. The results show that the design and development process started from adding color sensors and HMI from the system to be created. Then make modeling with the Festo Fluidsim application. After the capitalization is carried out, the hardware assembly is divided into two parts, namely the main and supporting hardware. The main hardware consists of a metal separator system, color separator and robotic arm, while the supporting hardware such as tables, conveyors and control panels. Once the hardware is complete, the PLC and HMI programs are made, the PLC uses MELSOFT Series GX Works2 software and the HMI uses Live Studio software. When the hardware and software are complete, testing and data collection of the tool work are carried out. Tool testing is carried out to determine the required bar pressure with a 100% success rate.